(untitled) (American Journal of Medical Science and Innovation, 2023)
Thyroid hormones have profound effects on reproduction. Normal thyroid function is necessary to maintain reproductive physiology, but its functional abnormalities may cause infertility manifesting as menstrual cycle irregularities. Aim of this research was to determine the serum levels of thyroid hormones in infertile and fertile women attending a tertiary care hospital in North-Central Nigeria. This comparative, reproductive medicine, cross-sectional study was carried out among one hundred and six (106) women attending the Gynecology Clinic of the Department of Obstetrics and Gynecology and the Family Planning Clinic of a tertiary care hospital in North-Central Nigeria. Women with a history suggestive of either primary or secondary infertility and the control women with no history of infertility were evenly grouped. Venous blood samples were collected and analyzed using Enzyme-Linked Immunosorbent Assay (ELISA) technique to determine fT3, fT4 and TSH levels. Data obtained were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 23, and the level of statistical significance was set at p<0.05 and at a confidence interval of 95% for all inferential statistics. Majority (90.6%) of the 106 participants were euthyroid. However, most of the thyroid disorders (80%) were noticed in the infertile women, as 15.1% of them had one form of thyroid disorder. The mean TSH, fT3 and fT4 levels were higher in the infertile patients than in the control group, but the values were still within normal reference range. Mean values of TSH, fT3 and fT4 for the patients and controls were 1.35±1.65 versus 0.85±1.08 mIU/mL, 2.79±1.51 versus 2.19±1.15 pg/mL, and 1.15±0.33 versus 0.99 ± 0.29 ng/dL respectively. Median for TSH, fT3 and fT4 in the patients and controls were as follows: 0.80 (0.40–1.55) versus 0.60 (0.40-0.85) mIU/mL, 2.40 (1.45-4.20) versus 1.70 (1.35-2.95) pg/mL, and 1.10 (1.00-1.30) versus 1.00 (0.90- 1.10) ng/dL respectively. The differences in the median between the patients and controls were statistically significant for fT3 and fT4 with p-values of 0.031 and 0.002 respectively. Subclinical hypothyroidism was the most prevalent (7.5%) thyroid disorder identified in the infertile women. Serum levels of thyroid hormones and prevalence of thyroid disorders were significantly higher in the infertile patients compared to the fertile women, although the overall prevalence of thyroid disorders was quite low.